2008
DOI: 10.3382/ps.2007-00231
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calcium and Phytate in Broiler Diets. 1. Effects on Apparent Prececal Digestibility and Retention of Phosphorus

Abstract: Phytate P utilization from soybean meal (SBM) included in broiler diets has been shown to be poor and highly dependent on dietary Ca intake. However, the effect of Ca on P utilization and on the optimal ratio of Ca to nonphytate P (Ca:NPP) when diets contained varying levels of phytate has not been clearly shown and was the objective of this research. A factorial treatment structure was used with 4 dietary Ca levels from 0.47 to 1.16% and 3 levels of phytate P (0.28, 0.24, and 0.10%). Varying dietary phytate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 25 publications
9
44
0
3
Order By: Relevance
“…High dietary calcium chelates part of the lipid fraction, which may reduce the energy value of the diet (Driver et al, 2005). Additionally, Ca forms insoluble complexes with phytate (Angel et al, 2002) and in the lumen interacts with inorganic phosphorus resulting in Ca-ortophosphate (Plumstead et al, 2008). Those complexes have a negative impact on the birds' performance due to the reduced solubility and availability of the P (Hamdi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…High dietary calcium chelates part of the lipid fraction, which may reduce the energy value of the diet (Driver et al, 2005). Additionally, Ca forms insoluble complexes with phytate (Angel et al, 2002) and in the lumen interacts with inorganic phosphorus resulting in Ca-ortophosphate (Plumstead et al, 2008). Those complexes have a negative impact on the birds' performance due to the reduced solubility and availability of the P (Hamdi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Phytate interacts with proteins (Liu et al, 2009), reducing its digestibility for broilers, reduces mineral absorption (Plumstead et al, 2008), and increases endogenous losses (Cowieson et al, 2004), characterizing it as an anti-nutrient for broilers (Cowieson et al, 2011). Phytase hydrolyzes the phytate molecule, releasing P and at the same time reducing the concentration and thus the anti-nutritional effects of phytate.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, besides being a possible source of P, phytate is also considered an anti-nutrient for broilers (Cowieson et al, 2011), reducing protein (Liu et al, 2009) and mineral absorption (Plumstead et al, 2008), increasing mucus production (Cowieson et al, 2004) and interfering with broiler performance (Linares et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tamim et al 41 reported that in the absence of dietary Ca broilers were able to degrade 69.2% phytate P by the terminal ileum; however, this was reduced to 25.4% when dietary Ca level was increased to 0.5%. Plumstead et al 42 observed that increasing Ca from 4.7 to 11.6 g kg −1 in broiler diets linearly decreased ileal phytate P digestibility by 71%. In laying hens, van der Klis et al 43 reported that increasing dietary Ca from 30 to 40 g kg −1 reduced phytate P degradation from about 33 % to 9% in the diet without phytase supplementation.…”
Section: Other Dietary Factorsmentioning
confidence: 99%